Fabrication of D–π–A sensitizers based on different donors substituted with a dihydropyrrolo[3, 4-c]pyrrole-1, 4-dione bridge for DSSCs: influence of the CDCA co-absorbent. (22nd June 2018) - Dhar, Abhishek; Siva Kumar, Nadavala; Asif, Mohammad; Vekariya, Rohit L.
Abstract : The effect of co-absorbance on the performance of DSSC devices with a new design of dimer sensitizers possessing a 2, 5-dihydropyrrolo[3, 4- c ]pyrrole-1, 4-dione (DPP) bridge and various donor groups (carbazole, diphenyl amine, indole) are reported in the present work. Abstract : The effect of co-absorbance on the performance of DSSC devices with a new design of dimer sensitizers possessing a 2, 5-dihydropyrrolo[3, 4- c ]pyrrole-1, 4-dione (DPP) bridge and various donor groups (carbazole, diphenyl amine, indole) is reported in the present work. The co-absorbent (CDCA = chenodeoxycholic acid) was inserted into the sensitizers and the photovoltaic performance was studied. The co-absorbent had a significant effect on J sc, V oc and the efficiency. Without incorporation of the co-absorbent, a higher efficiency of around 4.40% is exhibited ( J sc = 9.91 mA cm −2 and V oc = 0.678 V) by the R3 device, while after adding the co-absorbent, we have achieved an efficiency of around 4.44% ( J sc = 10.3 mA cm −2 and V oc = 0.693 V). Structure optimization and energy level calculations were carried out by density functional theory (DFT) with different donor substituents and DPP bridge based sensitizers. The co-absorbent and sensitizer based DSSCs were also characterised by impedance spectroscopy and incident photon to current conversion efficiency measurements.